Designing Digital Storyboards of Tangerang Folklore through Structural and Semiotic Approaches - Shenny Ayunuri Beata Sitinjak; Irpan Ali Rahman; Bayu Prasatya Sumarwoto; Ribka Fransisca; Hasan Daud (Journal of English Language and Education, 2026)
This study aims to analyze the narrative structure and symbolic meanings embedded in Tangerang folklore and to design a digital media prototype for preserving local cultural heritage. A descriptive qualitative approach was employed using the Research and Development (RD) method based on the ADDIE model, focusing on the analysis and design stages. Data were collected through literature review, field observations, and semi-structured interviews with community leaders and cultural informants in Tangerang. The data were analyzed using Vladimir Propp’s narrative structure theory and Roland Barthes’ semiotic framework to examine both story patterns and symbolic representations. The findings reveal that Tangerang folklore exhibits recurring narrative structures characterized by conflict, struggle, and symbolic resolution. Semiotic analysis further indicates that symbols such as monuments, irrigation canals, and the figure of the “Lioness” represent local identity, collective solidarity, ecological values, and female heroism. In addition, the study produced a Google Sites-based digital storyboard prototype featuring interactive story navigation, visual illustrations, and cultural content. The prototype demonstrates the potential of digital media as an innovative strategy for preserving and promoting local folklore in the digital era.